Ligand structure directed dimensionality reduction (2D -> 1D) in lead bromide perovskite - Bakthavatsalam, Rangarajan; Haris, Muhammed P. U.; Shaikh, Samir R.; Lohar, Amruta; Mohanty, Ashutosh; Moghe, Dhanashree; Sharma, Shivani; Biswas, Chinmoy; Raavi, Sai Santhosh Kumar; Gonnade, Rajesh G.; Kundu, Janardan (Journal of Physical Chemistry C, 2020)
Low dimensional (2D, 1D) lead halide perovskites are currently attracting huge research interest due to their enabling properties. Demonstrating synthetic control on the dimensionality/ structure of these perovskites is highly challenging. Dimensionality in these perovskites is largely dictated by the nature/structure and composition of the incorporating ligands and the utilized synthetic conditions. Here, we demonstrate chemical composition based control on reduction of dimensionality (2D -> 1D) for lead bromide perovskite utilizing 2-(2-aminoethyl)isothiourea dihydrobromide as a common precursor ligand (Isothio Bromide). Controlling the hydrothermal reaction parameters (temperature, time) at a fixed precursor ratio affords corner-shared, contorted 2D sheet perovskite and corner-shared, contorted, chiral 1D chain perovskite. Such dimensionality reduction leads to contrasting photophysical properties: 1D chain perovskite shows long-lived and self-trapped broad band emission, whereas 2D perovskite shows short-lived, band edge emission with a long tail. Mechanistic studies and single crystal structure analysis reveal the incorporation of the utilized precursor ligand (Isothio Bromide) in 2D perovskite. Surprisingly, the 1D perovskite is found to be chiral (P2(1) space group) incorporating 2-(2-aminoethyldisulfanyl)ethanamine and ammonium ions as the achiral ligands generated in situ due to hydrothermal cleavage of the precursor (Isothio Bromide) ligand. Such structural and compositional change of the ligands, which manifests a different hydrogen bonding network in the resultant perovskite structure, plays a decisive role in dictating the final molecular formula and dimensionality/structure of the perovskite which largely controls their photophysical properties.

Speed breeding opportunities and challenges for crop improvement - Sharma, Shivani; Kumar, Amit; Dhakte, Priyanka; Raturi, Gaurav; Vishwakarma, Gautam; Barbadikar, Kalyani M.; Das, B. K.; Shivaraj, S. M.; Sonah, Humira; Deshmukh, Rupesh (Journal of Plant Growth Regulation, 2023)
Crop improvement in light of the rapidly changing climate and the increasing human population continues to be one of the primary concerns for researchers across the globe. The rate at which current crop improvement programs are progressing is essentially inadequate to meet the food demand. There is an urgent need for redesigning the crops for climate resilience and sustainable yield and nutrition. The rate of crop improvement is largely impeded owing to the long generation time taken by crop plants during the breeding process. As a solution in this direction, speed breeding is now being practiced at a large scale to reduce generation time to accommodate multiple generations of crops per year. To enhance the efficiency of breeding, researchers are now adopting an integrated approach where speed breeding is used along with modern plant breeding and genetic engineering technologies. In the present review, we have summarized the technological aspects, opportunities, and limitations associated with speed breeding. The application of speed breeding such as mapping population development, haplotype-based breeding, transgenic breeding, and genome-edited line advancement has also been discussed. Speed breeding is a promising technology that expedites the goals of food and industrial crop improvement by reducing the breeding cycles for establishing nutritional security and sustainable agriculture.
Keywords: Genome editing; Genomic selection; Haplotype breeding; Speed breeding; Transgenic breeding

Article chitinase inhibition induces transcriptional dysregulation altering ecdysteroid-mediated control of spodoptera frugiperda development - Barbole, Ranjit S.; Sharma, Shivani; Patil, Yogita; Giri, Ashok P.; Joshi, Rakesh S. (Iscience, 2024)
Chitinases and ecdysteroid hormones are vital for insect development. Crosstalk between chitin and ecdysteroid metabolism regulation is enigmatic. Here, we examined chitinase inhibition effect on Spodopsilencing and overexpression resulted in ecdysone receptor deregulation. Transcription factors, like Neverland, and other ecdysteroid biosynthesis genes might lead to their upregulation in berberine-fed chitinase activity's impact on ecdysone biosynthesis and its transcriptional crosstalk.